Pemetaan Konseptual Nur Muhammad Menurut Perspektif Kosmologi Sufi dan Kosmologi Fizik: Conceptual Mapping of Nur Muhammad according to Sufi And Physic Cosmology - Mohammed Zabidi, Ahmad Fakhrurrazi; Wan Razali, Wan Qashishah Akmal; Radiman, Shahidan; Samian, Abdul Latif (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
The insight of the ‘light of Muhammad’ as primordial light and First Creation of Allah SWT has been discussed in the field of Sufism. It is one of the subdivisions of the Wahdah al-Wujūd (Oneness of Being). However, the debate on the concept of this Sufi cosmology as viewed from scientific knowledge is still scarce. The present study entailed a reexamination of the conceptual mapping of the Sufi cosmology in the scientific framework in which science-based on Divine values. Science, notably the physical cosmology much described in the Western perspective, do not emphasize the Divine aspects so most of them lead to unbelieve in the existence of God. Taken together with an introductory mapping or comparative study between both perspectives namely theology and science, this study tried to shed light on the ontology of the Haqiqat al-Muhammadiyyah (intrinsic, Muhammadan Reality) and on the superiority of Prophet Muhammad PBUH as keys in establishing the relationship of mankind in the diverse aspect of life to the Creator. Although the concept of Nūr Muhammad is speculative through the kashf of the Sufis as the Big Bang theory is also not an absolute among Western astrophysicists, the findings from this comparative study open the discourse for future studies related to the concept of Nūr Muhammad via deeper science in the Islamic Science worldview through the approach of the Lata’if Qur’aniyah which focuses on the aspect of connectedness between servants and Allah SWT.